2018
DOI: 10.2147/ott.s174524
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of long non-coding RNA AOC4P on gastrointestinal stromal tumor cells

Abstract: ObjectiveIn this research, we explored the effect of long non-coding RNA (lncRNA) AOC4P on gastrointestinal stromal tumor (GIST) cells.Materials and methodsThe expression of lncRNA AOC4P in tissues was detected by real-time PCR (RT-PCR). The epithelial–mesenchymal transition (EMT)-related proteins in tissues were analyzed by Western blot. The experiment included negative control group (CN), silence AOC4P group (si AOC4P), and silence negative control group (si CT). RT-PCR, MTT, Scratch, Transwell, and Annexin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…RASSF4 is a member of the RASSF family of tumor suppressors. AOC4P is a lncRNA involved in Hepatocellular Carcinoma and Colorectal Cancer [22] and ADHFE1 is a breast cancer oncogene [41].…”
Section: Resultsmentioning
confidence: 99%
“…RASSF4 is a member of the RASSF family of tumor suppressors. AOC4P is a lncRNA involved in Hepatocellular Carcinoma and Colorectal Cancer [22] and ADHFE1 is a breast cancer oncogene [41].…”
Section: Resultsmentioning
confidence: 99%
“…The exact roles of UPAT in the EMT process is divergent in cancer types 15‐17 . Based on bioinformatics analysis and the correlation between UPAT expression and MVI, we preliminarily discovered that UPAT not only inhibits the EMT process, but also controls the acquisition of CSC properties by suppressing the expression of CSC‐related TFs and markers.…”
Section: Discussionmentioning
confidence: 99%
“…Taniue et al 14 first reported the oncogenic effect of UPAT in colon tumorigenesis by inhibiting TrCP‐mediated UHRF1 degradation but, unfortunately, UPAT expression was not evaluated in colon cancer tissues. In gastric cancer and gastrointestinal stromal tumors, UPAT was thought to be upregulated in tumor tissues and positively correlated with greater proliferative, migrative, and invasive abilities, as well as the transition from epithelial to mesenchymal states 15,16 . Another study, however, reported that UPAT was significantly downregulated in HCC and negatively correlated with worse clinicopathological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs have been shown to play important roles in the regulation of various biological processes and the development of various diseases [25]. Several lncRNAs identi ed in other malignant tumors, such as HOTAIR, CCDC26, and AOC4P, have also been evaluated in GISTs and were shown to be associated with GIST metastasis and sensitivity to imatinib [17,26,27]. Gyvyte et al performed a next-generation sequencing study of paired GISTs and adjacent tissue samples from 15 patients and identi ed two deregulated lncRNAs (H19 and FENDRR) in GISTs [28].…”
Section: Discussionmentioning
confidence: 99%